(3MdjI GdPgH GdCHQjR aj QMdI HYdHc hGdHbGY GdYRjRs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR bOQ GdHbGY HeG ChOY ajgG ef Cgd GdGQJbGA s
(3BNQgG (B:s
(3aEf Gdcd eNdhb HGdMb MJi GddYH hGddgh hGdNWC hGdSgh s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B420s
Keywords: (3GdLZQGajG h GdHdOGfs